2012
DOI: 10.1016/j.geomorph.2012.08.021
|View full text |Cite
|
Sign up to set email alerts
|

‘Structure-from-Motion’ photogrammetry: A low-cost, effective tool for geoscience applications

Abstract: High-resolution topographic surveying is traditionally associated with high capital and logistical costs, so that data acquisition is often passed on to specialist third party organizations. The high costs of data collection are, for many applications in the earth sciences, exacerbated by the remoteness and inaccessibility of many field sites, rendering cheaper, more portable surveying platforms (i.e. terrestrial laser scanning or GPS) impractical. This paper outlines a revolutionary, low-cost, userfriendly ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
2,434
3
92

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 3,263 publications
(2,544 citation statements)
references
References 56 publications
15
2,434
3
92
Order By: Relevance
“…Orthomosaics were generated using Agisoft PhotoScan Professional (Agisoft LLC). The software reconstructs a three-dimensional point cloud from overlapping single images with a technique called Structure from Motion (Westoby et al 2012; Fonstad et al 2013; Smith, Carrivick, and Quincey 2016). In the first step, image alignment, information from the GPS unit of the UAS was used as a first estimate of camera location and orientation.…”
Section: Methodsmentioning
confidence: 99%
“…Orthomosaics were generated using Agisoft PhotoScan Professional (Agisoft LLC). The software reconstructs a three-dimensional point cloud from overlapping single images with a technique called Structure from Motion (Westoby et al 2012; Fonstad et al 2013; Smith, Carrivick, and Quincey 2016). In the first step, image alignment, information from the GPS unit of the UAS was used as a first estimate of camera location and orientation.…”
Section: Methodsmentioning
confidence: 99%
“…3-D photo-reconstruction (3D-PR) based on structure-frommotion (SfM) algorithms has been applied to date to a large number of geoscience applications (James and Robson, 2012;Westoby et al, 2012;Fonstad et al, 2013). Although there has been a great advance in the last years regarding imagery collection (for instance, derived from the development of UAV (unmanned aircraft vehicle) platforms) and image processing (commercial as well as free software), the complete photo-reconstruction (PR) and analysis workflow frequently remains lengthy and not straightforward (Kaiser et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Procedures for obtaining imagery using unmanned platforms and processing acquired data in photogrammetric software no longer require expert knowledge and experience. The high degree of automation in photogrammetric flight planning and execution and the availability of numerous software packages utilizing SfM algorithms make the extraction of threedimensional coordinates from sufficiently overlapping photography possible (Tonkin et al, 2014) even without camera location and orientation data (Snavely et al, 2008;Westoby et al, 2012). It has been demonstrated that this approach produces terrain models with resolution and data quality equivalent to or better than lidar (Carrivick et al, 2013;Fonstad et al, 2013).…”
Section: Introductionmentioning
confidence: 99%